SHARK FIN RAYS-TECHNOLOGY OF EXTRACTION. - RAMACHANDRAN NAIR, K G; MADHAVAN, P (Fishery Technology, 2017)
A simple process is described for extraction of rays fromshark fins. The process consists in treating the rays withacetic acid to soften the tissue, separation. of the rays by handand drying. White fins yield almost double the quantity ofrays compared to black fins.